Practical Analysis of Cognitive Theory on Early Childhood Development - Heldanita Heldanita; Welli Marlisa; Novriti Ramadora; Nurhasanah Bakhtiar; Nurkamelia Mukhtar; Nurhayati Nurhayati; Winda Trimelia Utami (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2022)
The background of this research is the lack of attention to the achievement of early childhood cognitive development indicators. The purpose of this study is to provide information about cognitive theories and how they are practical in early childhood development. This research method uses descriptive research with a qualitative approach. Data collection techniques used are observation and documentation. The results showed that the observed 3-year-old children had developed according to age based on indicators on developmental standards. The child is already able to function the material mind and instinctive mind, but the mustafat reason is not yet. In accordance with Piaget's theory, the observed children are at the symbolic thinking stage and the Potential Development (PD) stage, and the iconic stage (3-5 years). The methods used by parents to stimulate children's cognitive development were observed including: a) Conversational Method, b) Question and answer method, c) Conversation method, d) Demonstration method. The new kid arrives at skill C4 in Bloom's theory. Then the child is also able to demonstrate critical thinking skills, creative, metacognition, mathematics and science.Keywords: Analysis, Cognitive Theory, Early Childhood